2017
DOI: 10.1080/21663831.2017.1336496
|View full text |Cite
|
Sign up to set email alerts
|

Interface structures and twinning mechanisms of twins in hexagonal metals

Abstract: A controversy concerning the description of {1012} 1011 twinning, whether it is shear-shuffle or pure glide-shuffle or pure shuffle, has developed. There is disagreement about the interpretation of transmission electron microscopic observations, atomistic simulations and theories for twin growth. In this article, we highlight the atomic-level, characteristic, equilibrium and non-equilibrium boundaries and corresponding boundary defects associated with the threedimensional 'normal', 'forward' and 'lateral' prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 104 publications
3
52
0
Order By: Relevance
“…When a TD loop nucleates on the normal-TB, the twin thickens by two atomic layers. The migration of forward and lateral TBs is accomplished via glide of TD loops 34 along η 1 and λ directions. The segment of a TD loop parallel to λ is perpendicular to the Burgers vector and has pure edge character.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When a TD loop nucleates on the normal-TB, the twin thickens by two atomic layers. The migration of forward and lateral TBs is accomplished via glide of TD loops 34 along η 1 and λ directions. The segment of a TD loop parallel to λ is perpendicular to the Burgers vector and has pure edge character.…”
Section: Discussionmentioning
confidence: 99%
“…The questions to be posed next are whether large coherent or semicoherent facets form, as twins become larger; and whether those facets can move and lead to twin propagation. Molecular dynamics (MD) simulations show that edge TDs pile up and form BP/PB steps/facets in the BS view, and screw TDs pile up and form T-PP1 (semicoherent interface with 5.68° twist angle) or/and T-PP2 (semicoherent interface with 7.42° twist angle) facets 34 . When twinning is accomplished by the migration of large facets, shuffling is simultaneously involved.…”
Section: Discussionmentioning
confidence: 99%
“…They found the "dark side" of a twin embryo is composed of coherent TBs and semi-coherent twist prismatic-prismatic boundaries. To explore the migration of the "dark side", Gong et al [48] developed the 3D twin embryo in MD simulations, and reported the motion of twist prismatic-prismatic boundaries through atomic shuffling as well as the pinning effect of misfit dislocations on such boundaries. Spearot et al [27] also showed that three-dimensional simulations are needed to capture disconnection terrace nucleation and growth processes that are essential for the migration of mature TBs (i.e., larger TBs which can be approximated as flat interfaces, without considering bounding PB/BP interfaces, grain boundaries, or surfaces).…”
Section: Discussionmentioning
confidence: 99%
“…Such extraordinary peaks are therefore related to extended atomic configurations (interface core) inside the polycrystalline Mg. Since grains are individual single crystals, the regular atomic configurations that generate diffraction peaks which are not bulk related can only be found in interfaces such as grain boundaries, subgrain boundaries, twin boundaries and twist transition boundaries (Gong et al, 2017;Zhang et al, 2012;Li et al, 2011).…”
Section: Synchrotron Xrd Measurementsmentioning
confidence: 99%
“…Progress has been made in improving desirable properties through alloying (Zhu & Chen, 2019;Trang et al, 2018), thermomechanical processing (Zeng et al, 2017;Huang & Langdon, 2013) and incorporation of reinforcing phases producing metal-matrix composites (Chen et al, 2015), but knowledge of the interface structure down to nanoscale is also crucial for designing materials with new regimes of propertyperformance space (Oganov et al, 2019;Hu et al, 2018;Beyerlein et al, 2015). The interface structure of polycrystalline metallic materials, such as grain boundaries, subgrain boundaries, twin boundaries and twist transition boundaries (Gong et al, 2017;Zhang et al, 2012;Li et al, 2011), strongly influences mechanical (Zhu & Chen, 2019;Liu et al, 2014), electronic/optoelectronic (Hu et al, 2018) and thermal properties. Moreover, interfaces significantly affect diffusion kinetics and consequently mass transport, being thus fundamental to understanding phenomena such as hydrogen embrittlement (Uberuaga et al, 2015) and radiation damage evolution (Jiang & Szlufarska, 2018;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%